Anti-gliadin antibodies in patients with celiac disease cross-react with enterocytes and human calreticulin - Tucková, L; Karská, K; Walters, J R; Michalak, M; Rossmann, P; Krupicková, S; Verdu, E F; Saalman, R; Hanson, L A; Tlaskalová-Hogenová, H (Clinical immunology and immunopathology, 1997)
One of the characteristic features of celiac disease is an increase in anti-gliadin antibodies (Abs). Recently we found that some of the monoclonal Abs to gliadin cross-react with molecules on rat enterocytes. One of these cross-reacting molecules was identified as rat calreticulin. This study shows that the levels of serum IgA Abs to gliadin, rat, and human enterocytes; purified enterocyte antigens; and calreticulin in sera from patients with active disease were significantly higher than in patients on a gluten-free diet and healthy controls (P < 0.001). Anti-gliadin Abs were isolated by affinity chromatography from the sera of six active celiac patients. The reactivity of these anti-gliadin Abs was demonstrated to be significantly higher (P < 0.05) with human enterocytes and human calreticulin than with other antigens tested. Furthermore, using isolated patients' anti-gliadin Abs bound to Sepharose 2B, two main proteins of molecular mass 62 and 66 kDa were purified from a lysate of human enterocytes. The 62-kDa enterocyte antigen was identified as human calreticulin. These findings suggest that anti-gliadin Abs may play a pathogenic role in celiac disease by cross-reacting with enterocytes. Calreticulin in enterocytes may be one of the putative targets for autoimmune reactions.
Keywords: sekvence aminokyselin; Antigens; lidé; mladiství; Adult; Middle Aged; ELISA; ribonukleoproteiny; Celiac Disease; protilátky; Infant; Female; dítě; krysa rodu Rattus; Enzyme-Linked Immunosorbent Assay; kalretikulin; Calcium-Binding Proteins; Adolescent; imunohistochemie; Humans; gliadin; potkani Wistar; Antibodies; Immunohistochemistry; předškolní dítě; Rats, Wistar; lidé středního věku; Child, Preschool; Calreticulin; mužské pohlaví; zvířata; celiakie; proteiny vázající vápník; zkřížené reakce; ženské pohlaví; Rats; Animals; imunoglobulin A; molekulární sekvence - údaje; Male; Aged; Molecular Sequence Data; Cross Reactions; Ribonucleoproteins; Gliadin; antigeny; Child; Immunoglobulin A; dospělí; Amino Acid Sequence; kojenec; senioři